E-Loyalty Analysis on Digital Banking Application Bank Jago - Moses Natadirja; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2022)
This Study purpose is to know whether Perceived Value from a digital banking applications can impacting E-Trust that leads to E-Satisfaction and E-Loyalty. This research using survey method to collect data with questionnaire method to Bank Jago’s user with convenience sampling technique. In this research, Partial Least Square-Structural Equation Modelling (PLS-SEM) is being used to running the data with SmartPLS 3.3.3 software. The results of this research is Perceived Value from Quality value, Social Value, and Emotional Value are positively impact on E-Trust, E-Trust positively impact on E-Satisfaction and E-Loyalty, and E-Satisfaction positively impact on E-Loyalty. Only Monetary value that is been part of Perceived Value is not positively impact on E-Trust.